Root canal treatment of a maxillary second molar with four mesiobuccal root canals - a case report - Nogueira,Flávia Cracel (2022)
Abstract Among the roots of maxillary molars, the mesiobuccal often presents with a root canal system that may be complex and variable, leading to a greater challenge when trying to achieve a proper chemo-mechanical preparation. The present report intends to show a successful root canal treatment of a maxillary second molar with six root canals, of which four were present in the mesiobuccal root. After being diagnosed with pulp necrosis and symptomatic apical periodontitis, a molar was endodontically treated. It also had an uncommon paracone cusp. A careful inspection of the pulp chamber floor revealed a mesiopalatal sulcus, which, after exploration with ultrasonic tips under an operating microscope magnification, showed three additional mesiobuccal root canals. After proper mechanical debridement, disinfection with sodium hypochlorite, and warm gutta-percha obturation, a favorable outcome was observed at the 12-month follow-up.